Contractual employment protection and the scarring risk of unemployment - Elke J. Jahn; Thomas Wagner (Institute for the Study of Labor (IZA), 2005)
Risk-averse job seekers fearing the scarring effect of unemployment meet vacancies offering contractual employment protection (CEP) in form of guaranteed employment (GEC) or severance pay contracts (SPC). A GEC fully eliminates both the income risk and the scarring risk of unemployment. SPC diversify the income risk, but provide only limited protection against the scarring risk. (1) Workers strictly prefer contract market to spot market jobs. (2) A higher productivity, a lower probability of demand shocks or of finding a re-employment after a dismissal as well as lower public unemployment benefits increase the fraction of workers concluding a GEC. (3) Although firms are risk-neutral, first-best SPC are not incentive compatible under asymmetric information on the demand for the output of the job. In the second-best equilibrium, a positive fraction of over-insured workers will conclude a GEC, while workers signing a SPC incur income risk. (4) With asymmetric information on the reemployment status of a dismissed worker, employees who conclude a third-best SPC face both uninsurable income risk and the unemployment scar. Workers with a precautionary motive who expect a large or long lasting scar, conclude SPC with wage replacement rates strictly larger than one and low recession wages, which make their jobs more viable.
Keywords: J31; J32; J81; 330; scarring effect of unemployment; contractual employment protection; guaranteed employment contract; severance pay contract; implicit contract; moral hazard; prudence